Efficient synthesis of lower rim α-hydrazino tetrazolocalix[4]arenes via an Ugi-azide multicomponent reaction1. (27th August 2015) - Alavijeh, Nahid S.; Zadmard, Reza; Ramezanpour, Sorour; Balalaie, Saeed; Alavijeh, Mohammad S.; Rominger, Frank
<x xml:space="preserve">Abstract</x> Herein, we developed an efficient synthesis of α-hydrazino tetrazolocalix[4]arene derivatives, suitable for metal ion complexation as investigated, via an Ugi-azide multicomponent reaction.